Development of reproductive potential in protogynous coral reef fishes within Philippine no‐take marine reserves. Issue 5 (12th August 2021) - Bucol, Abner A.; Abesamis, Rene A.; Stockwell, Brian L.; Lowe, Jake R.; Russ, Garry R.
ABSTRACT: Empirical evidence for increases in the reproductive potential (egg output per unit area) of coral reef fish in no‐take marine reserves (NTMRs) is sparse. Here, we inferred the development of reproductive potential in two species of protogynous reef fishes, Chlorurus bleekeri (Labridae: Scarinae) and Cephalopholis argus (Epinephelidae), inside and outside of Philippine NTMRs. We estimated key reproductive parameters and applied these to species‐specific density and length data from 17 NTMRs (durations of protection 0–11 years) and paired fished sites (controls) in a space‐for‐time substitution approach. For C. argus, we also used density and length data collected almost annually over 29 years from a NTMR and an adjacent control at Apo Island. The results suggest that C. bleekeri can develop 6.0 times greater reproductive potential in NTMRs than controls after 11 years of protection, equivalent to approximately 582, 000 more eggs produced 500 m −2 inside NTMRs. Enhancement of reproductive potential in C. argus was not evident after 11 years in the space‐for‐time substitution. At Apo Island NTMR, reproductive potential of C. argus increased approximately 6‐fold over 29 years but NTMR/control ratios in reproductive potential decreased through time (from 3.2 to 2.4), probably due to spillover of C. argus from the NTMR to the control. C. argus was estimated to produce approximately 113, 000 more eggs 500 m −2 inside Apo Island NTMR at the 29th year of protection. Ratios of reproductive potential between NTMR and controls in C. bleekeri and C. argus were often greater than corresponding ratios in density or biomass. The study underscores the importance of species‐specific reproductive life history traits that drive variation in the development of larval fish subsidies that originate from NTMRs.